Policy evaluation of PT. Pindad in fulfilling the need for weapons and ammunition of the Army in the 2019-2022 period - Octovianus Oskar Engelberth; Runturambi, Arthur Josias Simon; Ras, Abdul Rivai (Technium Social Sciences Journal, 2023)
The problem studied in this study is the fulfillment of the needs for weapons and ammunition for the TNI AD at PT Pindad, the purpose of writing this article is to find out what weapons and ammunition products are capable of being produced and the level of productivity in producing these products to support the needs of the TNI AD. Indonesia’s participation, especially the TNI AD, in the ASEAN Armies Rifle Meet (AARM) competition which was held from 1991 to 2019 has recorded Indonesia as Champion 13 times. This can be interpreted that Indonesia is trying to maintain its championship position of 46.43% of the total championships that are participated in, in this case it is clear that PT Pindad’s domestic products are able to compete internationally. The direction of PT PINDAD’s policy in fulfilling the need for weapons and ammunition, especially for the Indonesian Army, is carried out on the basis of the concept of capability-based defense by considering possible threats to be faced and trends in the development of the strategic environment, its implementation is directed towards achieving Minimum Essential Force (MEF) strength. This research was conducted using a qualitative approach. Data were obtained through practical interviews with several sources. In addition, secondary data was obtained from search results from books, journals, official documents, official websites and other reliable sources. The result of the research is to find out the policies implemented by PT Pindad in meeting the needs of the TNI AD weapons and ammunition, especially if it is supported by policies and commitments that are in line with the TNI to meet the needs of the TNI AD weapons and ammunition.